Palicourea tomentosa (Aubl.) Borhidi: Microscopy, chemical composition and the analgesic, anti-inflammatory and anti-acetylcholinesterase potential. (12th June 2022) - Nazari Formagio, Anelise Samara; Vilegas, Wagner; Ferreira Volobuff, Carla Roberta; Leite Kassuya, Candida Aparecida; Paes de Almeida, Valter; Manfron, Jane; Pereira, Zefa Valdevina; Pereira Cabral, Marcia Regina; Sarragiotto, Maria Helena
Abstract: Ethnopharmacological relevance: Palicourea tomentosa (Aubl.) Borhidi (synonym Psychotria poeppigiana Müll. Arg.) leaves are used in the popular treatments of inflammation and pain; however, there are no scientific studies demonstrating their activity as the methanolic extract of P. tomentosa. Aim of study: This study was undertaken to investigate the potential antioxidant, anti-acetylcholinesterase, anti-hyperalgesic, anti-nociceptive and anti-inflammatory properties, as well as the chemical composition and concentrations of constituents of the methanolic extract of P. tomentosa leaves (MEPT). The study also analyzes the micromorphology and histochemistry of leaves of P. tomentosa . Materials and methods: The MEPT was analysed by ultra-high-pressure liquid chromatography-high resolution mass spectrometry (UHPLC-HRMS/MS). The concentrations of total phenols, flavonoids, flavonols and condensed tannin were determined. The micromorphology and histochemistry of leaves were performed using standard reagents, light and field emission scanning electron microscopy, beyond energy-dispersive X-ray spectroscopy. The antioxidant activity was evaluated for DPPH, β-carotene and MDA. The anti-inflammatory activity of MEPT (30, 100, and 300 mg/kg) was assayed in carrageenan-induced models of paw oedema, mechanical hyperalgesia (Von Frey), cold allodynia (acetone) and pleurisy in mice. The anti-nociceptive potential of MEPT (30, 100, and 300 mg/kg) was evaluated by the formalin method in mice. The anti-acetylcholinesterase properties were evaluated in vivo in four rat brain structures. Results: The total ion chromatogram of MEPT demonstrated two alkaloids, one coumarin, one iridoid and two terpene derivatives. The highest phenol, flavonoid, flavonol and condensed tannin concentrations were found in the extract. A comprehensive explanation of the leaf micromorphology and histochemistry was presented. MEPT was significantly inhibited by the DPPH, β-carotene and MDA models. MEPT (30, 100 and 300 mg/kg) reduced the inflammation and hyperalgesic parameters in a carrageenan model and reduced formalin-induced nociception in both phases, which were cold sensitivity and oedema formation. The oral administration of 30 and 100 mg/kg MEPT significantly inhibited AChE activity in the frontal cortex. Conclusion: This is the first chemical and biological study performed with a P. tomentosa methanolic extract and anatomical and histochemical analysis. The present study showed that MEPT inhibited pain and inflammatory parameters contributing, at least in part, to explain the popular use of this plant as analgesic natural agent. Also, anatomical and histochemistry of leaves described in the present study provide microscopical information, which aids species identification. Graphical abstract: Image 1